In quest of the science in statistical fault localization. (11th November 2011) - Chan, W. K.; Cai, Yan
SUMMARY: Many researchers employ various statistical methods to locate faults in faulty programs. Like other researchers, we sometimes have made mistakes in the quest of making statistical fault localization both practical and scientific. In this experience report, we reflect on our work conducted on this topic, organize our isolated experiences in the format of models and errors, and cast them in the context of statistics. Copyright © 2011 John Wiley & Sons, Ltd.